Fundamental determinants of real estate prices: A panel study of German regions - Ansgar Belke; Jonas Keil (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
This paper aims at establishing empirical facts on the fundamental determinants of real estate prices. It contributes to the literature by analysing a unique panel dataset covering a wide range of real estate market data and other economic variables for nearly 100 German cities. Several robust fundamental determinants are identified, among them the supply-side factors construction activity and housing stock as well as the demandside factors apartment rents, market size, age structure, local infrastructure and rental prices. Results suggest that these factors are robustly linked to fundamental real estate prices and thus can be used to detect misalignments of market prices. – – Dieser Beitrag zielt darauf ab, empirische Evidenz über die fundamentalen Determinanten der Immobilienpreise zu etablieren. Es trägt zur Literatur bei, indem es einen einzigartigen Panel-Datensatz analysiert, der eine breite Palette regionaler Immobilienmarktdaten und anderen ökonomischen Variablen für fast 100 deutsche Städte umfasst. Wir identifizieren unter diesen mehrere robuste fundamentale Determinanten der regionalen deutschen Immobilienpreise. Dabei handelt es sich um die angebotsseitigen Faktoren Bautätigkeit und Immobilienbestand sowie die nachfrageseitigen Faktoren Wohnungsmieten, Marktgröße, Altersstruktur, lokale Infrastruktur und allgemeine Immobilien-Mietpreise. Unsere Untersuchungsergebnisse deuten darauf hin, dass diese Faktoren stark mit den fundamentalen Immobilienpreisen verknüpft sind und somit dazu genutzt werden können, fundamentale Fehlentwicklungen der Marktpreise frühzeitig zu erkennen.
Keywords: R21; R31; 330; real estate market; fundamental prices; regional data; panel study